2024
DOI: 10.61579/beujroh.v2i1.71
|View full text |Cite
|
Sign up to set email alerts
|

Pemberdayaan Masyarakat Melalui Pengembangan Keterampilan Merajut Dalam Upaya Peningkatan Pendapatan Keluarga

Nikmatul Masruroh,
Muhammad Sadhie

Abstract: This community service has the first goal, assistance in the process of developing knitting skills, second, assistance in community empowerment so as to increase family income. This service is carried out using the ABCD (Asset Based Community Development) method, namely service with the stages of finding, dreaming, designing, determining and doing. So that this service produces the first asset in the form of the ability to make knitting in the community developed with training and innovation of knitting produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Based on the definition of empowerment that has been mentioned, it can be concluded that empowerment is a series of activities to enrich knowledge and strengthen the empowerment of vulnerable and weak groups in society, including individuals who experience poverty problems [29]. By empowering groups or individuals who are vulnerable, such as lack of knowledge and problems of poverty, it makes them stronger and more empowered in meeting their life needs both physically, economically and socially, such as: being able to express their aspirations, being more confident [30].…”
Section: Community Empowermentmentioning
confidence: 99%
“…Based on the definition of empowerment that has been mentioned, it can be concluded that empowerment is a series of activities to enrich knowledge and strengthen the empowerment of vulnerable and weak groups in society, including individuals who experience poverty problems [29]. By empowering groups or individuals who are vulnerable, such as lack of knowledge and problems of poverty, it makes them stronger and more empowered in meeting their life needs both physically, economically and socially, such as: being able to express their aspirations, being more confident [30].…”
Section: Community Empowermentmentioning
confidence: 99%